Antarctic antics-- and more hilarious animal stories! [videorecording (DVD)] - Sierra, Judy; Fleming, Denise, 1950-; Wilson, Karma; Feiffer, Jules; Slobodkina, Esphyr, 1908-2002; Ungerer, Tomi, 1931-2019- (Scholastic storybook treasures., 2007)
#1: Sing along with a chick as she grows up and learns about life on a penguin colony in Antarctica. #2: The natural beauty of animal life in a pond is depicted through striking illustrations and bewitching blends of words and sounds. #3: Some animals stop by a cave to warm up from the snow, drink tea and eat popcorn. What will Bear do when he wakes up to a lair of noisy guests? #4: When George, a dog, is told to bark he says "meow" and "quack-quack" and "oink" and "moo." Can the vet help George bet his bark back? #5: A peddler falls alseep under a tree and awakens to find that all of his colorful caps are gone. #6: A magical hat with a mind of its own goes on daring rescues and changes the life of a penniless man. #7: A lighthouse learns that you can still be important even if you are small.